An Activity‐Based Sensing Fluorogenic Probe for Monitoring Ethylene in Living Cells and Plants. (26th August 2021) - Chen, Yiliang; Yan, Wei; Guo, Duojing; Li, Yu; Li, Ji; Liu, Hao; Wei, Lirong; Yu, Na; Wang, Biao; Zheng, Ying; Jing, Maofeng; Zhao, Jing; et al.
Abstract: Ethylene (ET) is an important gaseous plant hormone. It is highly desirable to develop fluorescent probes for monitoring ethylene in living cells. We report an efficient Rh III ‐catalysed coupling of N ‐phenoxyacetamides to ethylene in the presence of an alcohol. The newly discovered coupling reaction exhibited a wide scope of N ‐phenoxyacetamides and excellent regioselectivity. We successfully developed three fluorophore‐tagged Rh III ‐based fluorogenic coumarin‐ethylene probes (CEPs ) using this strategy for the selective and quantitative detection of ethylene. CEP‐1 exhibited the highest sensitivity with a limit of detection of ethylene at 52 ppb in air. Furthermore, CEP‐1 was successfully applied for imaging in living CHO‐K1 cells and for monitoring endogenous‐induced changes in ethylene biosynthesis in tobacco and Arabidopsis thaliana plants. These results indicate that CEP‐1 has great potential to illuminate the spatiotemporal regulation of ethylene biosynthesis and ethylene signal transduction in living biological systems. Abstract : Fluorophore‐tagged Rh III ‐based fluorogenic probes were developed for rapid (<2 min), highly selective, and quantitative detection of ethylene. Among the coumarin‐ethylene probes developed, CEP‐1 has the capacity to detect endogenous ethylene gas in living cells and plants.